Significance of Preventive Aspect of Unani Medicine in COVID 19 - Shiffa, M.S.M.; Fahamiya, N. (Unani Drugs Manufacturer Association, India, 2020)
Today’s world evidences the influence of lifestyle on human health in relation with the outcomes of Covid 19 management. As not like past, despite of highly equipped medical facilities, world suffers a lot to control and manage Covid – 19 as disease profile is changing rapidly and reduces the productivity of the entire globe. During the past several years, there has been a growing interest in the medical implications of finding remedies for infectious and non-infectious disease as conventional medicines failed to provide perfect solutions. As Unani system of medicine emphasizes the optimum function of tabi’at for the healthy life, the tabi’at is governed by the healthy life style. When tabi’at became weak, it leads to many diseases. not only lifestyle diseases such as cancer, cardiovascular diseases, arthritis, atherosclerosis, hypertension,but also other infectious diseases as well. In recent years, a multitude of studies provide comprehensive evidence that increased production of various substances produced in the body by unhealthy life styles (food and diet, less physical activities) which believed to weaken the immunity, so that body fails to prevent or fight against infections, cancers and lead to the development of lifestyle diseases which justifies the concepts of Unani medicine on diseases.Unani system of medicine emphasizes the maintenance of healthy life through implementing asbab-esittazarooriya (six essential factors). They influence on human body to generate a new state or maintain the persisting state and help in the promotion of health and prevention of diseases. A balanced relationship between the six essential factors keeps the humors and the temperament on the right track and due to their imbalance all mental and somatic diseases occur. Unani System does not only address the symptoms of lifestyle diseases, moreover, it identifies and deals with the underlying causes. Hence, by adoption of an appropriate Unani lifestyle plan we can strengthen the tabi’atand by that prevent and reduce the degree and severity of the diseases, thus ensuring a better quality of life
Keywords: lifestyle disorders; defense mechanism; Unani medicine; six essential factors